Prevalence and factors associated with body mass index in children aged 9-11 years - Gerson Luis de Moraes Ferrari; Victor Matsudo; Peter T. Katzmarzyk; Mauro Fisberg (Elsevier, 2017)
Objective: This study aimed to identify the prevalence and factors associated with body mass index (BMI) in children aged 9-11 years. Methods: The study is part of the International Study of Childhood Obesity Lifestyle and the Environment (ISCOLE). Body composition was determined using the bipolar bioimpedance technique. The mean BMI value was categorized as recommended by the World Health Organization. For seven consecutive days, participants used an accelerometer to objectively monitor sedentary behavior (SB) and moderate to vigorous physical activity. Individual factors (anthropometric and behavioral), family aspects, and family and school environment were provided by participants and parents and were analyzed by multilevel linear regression adjusted for gender, ethnicity, school, number of siblings, and total annual family income. Results: The mean BMI was 20.1 kg/m2, and 51.8% of the children were overweight/obese (50.3% boys, 53.4% girls, p = 0.014). Considering all participants, the associated factors of BMI were body fat percentage (BF%, β = 0.0216, p < 0.001) and screen time (ST, β = 0.0050, p = 0.006). In boys, the associated factors were BF% (β = 0.0209, p < 0.001), ST (β = 0.006, p = 0.036), and healthy eating policies or practices (β = 0.0276, p = 0.025). In girls, only BF% was associated (β = 0.0221, p < 0.001) with BMI. Conclusions: High prevalence of overweight/obesity was observed in children from São Caetano do Sul. Different associated factors were identified between the genders, with only BF% being common in both genders. Resumo: Objetivo: O objetivo deste estudo foi identificar a prevalência e os fatores associados do índice de massa corporal (IMC) em crianças de 9-11 anos de idade. Métodos: O estudo faz parte do International Study of Childhood Obesity Lifestyle and the Environment (ISCOLE). A composição corporal foi determinada pelo método da bioimpedância bipolar. O valor médio do IMC foi categorizado conforme sugerido pela Organização Mundial de Saúde. Durante sete dias consecutivos, os participantes usaram acelerômetro para monitorar objetivamente o comportamento sedentário (CS) e atividade física de moderada a vigorosa. Fatores associados individuais (antropométricos e comportamentais), aspectos familiares, ambiente familiar e escolar, foram preenchidos pelos participantes e pais e foram analisados pela regressão linear multi-nível ajustados para sexo, raça, escola, número de irmãos, e renda familiar total anual. Resultados: A média do IMC foi de 20,1 kg/m2, sendo que 51,8% das crianças estavam com excesso de peso/obesidade (50,3% meninos; 53,4% meninas; p = 0,014). Considerando todos os participantes, os fatores associados do IMC foram a porcentagem de gordura corporal (%GC; β = 0,0216; p < 0,001) e o tempo de tela (TT; β = 0,0050; p = 0,006). Nos meninos, os fatores associados foram a %GC (β = 0,0209; p < 0,001), TT (β = 0,006; p = 0,036) e políticas ou práticas de alimentação saudável (β = 0,0276; p = 0,025). Já nas meninas, somente a %GC foi associada (β = 0,0221; p < 0,001) com o IMC. Conclusões: Mostramos valores elevados de prevalência de excesso de peso/obesidade em crianças de São Caetano do Sul. Diferentes fatores associados foram identificados entre os sexos, sendo somente a %GC foi comum em ambos os sexos. Keywords: Body composition, Obesity, Children, Public health, Palavras-chave: Composição corporal, Obesidade, Crianças, Saúde pública